KEPEMIMPINAN SEKOLAH - Dinda Mega Putri Oktavianti; Anne Effane (KARIMAH TAUHID, 2023)
The purpose of this research is to find out how to describe the condition of implementing the leadership of the school principal in carrying out its function to improve school quality, to find out how school achievement can be achieved, to find out the leadership role of the school principal to face obstacles in carrying out his duties. The research method used is descriptive qualitative research. Data collection was obtained from information, places and activities of the principal's leadership activities, as well as documents. Data retrieval technique by searching for journal records and documents from several sources. Data validity test was carried out by applying source triangulation and method triangulation. The results of the research are in the form of the main findings, namely: 1) Improving the quality of learning is determined by how the principal can manage school management and the ability to determine the Vision, Mission, Educational Objectives, Strategies and Targets according to the situation and condition of the school. 2) Improving the quality of the principal's leadership competence in carrying out his duties and functions is largely determined by the principal's self-motivation and how he can manage Learning Input, organize the Learning Process, produce Learning Output. 3) Overall the condition of the principal in carrying out his duties and functions as an Educator (Educator), as a Manager, as an Administrator, as a Supervisor, as a Leader (Leader), as an Innovator, as a Motivator is very good so that the principal can be an example in carrying out his duties.